Safe Navigation of an Autonomous Robot in Dynamic and Unknown Environments - Kondratenko, Yuriy P.; Roshanineshat, Arash; Simon, Dan (Recent Developments in Automatic Control Systems, 2022)
For robots to become an efficient means for performing tasks, they need to navigate safely and effectively without supervision. This chapter is devoted to the problem of fuzzy control system design for mobile robots operating in dynamic environments with obstacles. The decision-making method, based on the transformation of radar-sensor information to fuzzy set "Obstacles" and robot's heading course to fuzzy set "Direction to Target Point," is considered. We also address the safety aspects of the proposed approach. The different scenarios of the working environment (with static and dynamic obstacles), the adjusted speed of the autonomous robot, and peculiarities of "robot-obstacle" interaction are the issues for discussion. The simulation results confirm the efficiency and safety of the robot's autonomous navigation in dynamic and unknown environments.